The Leibniz-Des Bosses correspondence - Leibniz, Gottfried Wilhelm, Freiherr von, 1646-1716 (Leibniz, Gottfried Wilhelm, Freiherr von, 1646-1716. Works., 2007)
This volume is a critical edition of the ten-year correspondence (1706-1716) between Gottfried Wilhelm Leibniz, one of Europe's most influential early modern thinkers, and Bartholomew Des Bosses, a Jesuit theologian who was keen to bring together Leibniz's philosophy and the Aristotelian philosophy and religious doctrines accepted by his order. The letters offer crucial insights into Leibniz's final metaphysics and into the intellectual life of the eighteenth century. Brandon C. Look and Donald Rutherford present 71 of Leibniz's and Des Bosses' letters in the original Latin and in careful English translation. Few of the letters have been translated into English before. The editors also provide extensive annotations, deletions, and marginalia from Leibniz's various drafts, and a substantial introduction setting the context for the correspondence and analysing the main philosophical issues.